Die Altstadtbereiche westdeutscher Grossstädte und ihr Wiederaufleben nach der Kriegszerstörung - Kraus, Theodor (ERDKUNDE, 1953)
As survivals from the middle ages the congested cores of many large European cities pose difficult problems in their urban geography, especially regarding present-day economy and traffic. In Germany all these city centres have been destroyed by air raids. Using as examples three Rhenish cities, Duisburg, Essen and Cologne, it it attempted to show what forces have been at work in the devastated city cores since 1945, in what forms the former „Altstadt (olden-city) has reemerged, and to what extent it still lies latent. Although these three city centres differ in location, size and nature of urban life, each of them has been able to re-attract a large share of its former functions, particularly in the sphere of business life — regardless of new planning. The traditional scene of medieval building and dwelling has, however, disappeared for ever.